2017
DOI: 10.1007/s00894-017-3275-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding weakly coordinating anions: tetrakis(pentafluorophenyl)borate paired with inorganic and organic cations

Abstract: Efficient design of ionic compounds requires a systematic understanding of cation-anion interactions. Weakening of electrostatic attraction is essential to increase the liquid range of the ionic compound and decrease its melting point. Here, we report simulations of the closest-approach cation-anion distances in a variety of ion pairs containing the tetrakis(pentafluorophenyl)borate (TFPB) anion. Small alkali cations (Li, Na) penetrate the TFPB core, whereas K and larger organic cations do not. In the latter c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The charge on the bulky TB – anion is primarily centered on the boron atom. 33 Thus, weakly coordinating TB – has a poor ability to compensate the positive charge on the cationic EDOT oligomers which consequently maintain a net positive charge. The radical coupling steps also result in the release of protons on the organic side of the ITIES (see the Supporting Information and Figure S1 ) that will be stabilized by the PEDOT thin film itself or by water present inside the film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The charge on the bulky TB – anion is primarily centered on the boron atom. 33 Thus, weakly coordinating TB – has a poor ability to compensate the positive charge on the cationic EDOT oligomers which consequently maintain a net positive charge. The radical coupling steps also result in the release of protons on the organic side of the ITIES (see the Supporting Information and Figure S1 ) that will be stabilized by the PEDOT thin film itself or by water present inside the film.…”
Section: Resultsmentioning
confidence: 99%
“…Continuous EDOT ·+ generation by IET and ensuing radical coupling steps ultimately lead to the formation of EDOT oligomers that also coordinate with TB – to maintain electroneutrality (Figure ai). The charge on the bulky TB – anion is primarily centered on the boron atom . Thus, weakly coordinating TB – has a poor ability to compensate the positive charge on the cationic EDOT oligomers which consequently maintain a net positive charge.…”
Section: Resultsmentioning
confidence: 99%
“…This is probably accounted by several reasons: (1) the delocalization of negative charge over a large anion such as [B(C 6 F 5 ) 4 ] − helps with the stabilization of the polaron and more importantly, could be favorable for the electrophilic attack reaction shown above, as revealed by Beljonne et al. through theoretical calculations, [ 17 ] and (2) the bulky structure of [B(C 6 F 5 ) 4 ] − leads to low negative electrostatic surface potential and reduces the electrostatic attractive force between it and the polaron, which is beneficial to obtain efficient ion pair dissociation or higher charge dissociation efficiency [ 22b,26 ] (see Figure 4c). Indeed, the doped P3HT films were seen to exhibit increasing activation energy with the decrease of the anion size according to temperature‐dependent conductivity measurements (Figure 4d), which is partly attributed to the increasing electrostatic binding energies between the generated polarons and the anions.…”
Section: Resultsmentioning
confidence: 99%
“…On other hand, it well demonstrated that low overall charge and high degree of charge delocalization with shielded negative charge over the entire anion so that no individual atom or group of atoms bears a high concentration of charge are the characteristics features of weakly coordinating anions [36]. Consequently, tetraphenylboron as an illustrative example can preclude strong ion pairing formation [37], which is an essential prerequisite for an ion exchanger based ion selective sensors [38]. Addtionally, the hindered steric accessibility of the [mCPP] + where the positive charge is located in the ring of [mCPP] + plays also a crucial role in an ion pair complexation.…”
Section: Membrane Response and Sensitivity Of The Sensorsmentioning
confidence: 99%